Pengaruh Tayangan Sinetron Anak Jalanan Terhadap Perilaku Agresif Murid SMP Muhammadiyah 6 Surabaya (Faculty of Communications Science, Dr. Soetomo University, 2017)
This research is to know the effect from Anak Jalanan sinetron in RCTI against aggressive behavior from student of Muhammadiyah 6th Junior High School Surabaya. Especially the problem on television shows is “Anak Jalanan” which is had to many fans from Indonesia person for this time. No exception the students from Muhammadiyah 6th Junior High School Surabaya. The impressions seem to have ceased to provide positive benefits to the community, which often features battle scenes between other motor groups, then they always shown another scenes with arrogan, sly, and cruel character. This thing of course can change their behavioural effect like a bad bahavioural, it shown by behave to see bad sinetron. This research uses Spearman’s correlation coefficient data analysis technique. As for measuring instrument in research of independent variable (x), Namely the concept of impressions or exposure to Anak Jalanan’s sinetron violence, and for find the effect use SOR theory. While the measuring instrument on the dependent variable (Y) is using Youth Aggressiveness to study problems in adolescents, as well as procedures in certain societies and situations including relationships, activities, attitudes, views and ongoing processes and the effects of a phenomenon including the Anak Jalanan’s Show. Keywords: Perception, Sinetron, Anak Jalanan, Agresivitas